Autophagy in inflammatory bowel disease: immunization, etiology, and therapeutic potential - Miao, Zhong-Xing; Meng, Huan; Wang, Jie; Hou, Xiao-Ting; Cheng, Wen-Wen; Liu, Bao-Hong; Zhang, Qing-Gao; Yuan, Shuo (Frontiers in Immunology, 2025)
Please confirm that the below Frontiers AI generated Alt-Text is an accurate visual description of your Figure(s). These Figure Alt-text proposals won't replace your figure captions and will not be visible on your article. If you wish to make any changes, kindly provide the exact revised Alt-Text you would like to use, ensuring that the word-count remains at approximately 100 words for best accessibility results. Further information on Alt-Text can be found here.Inflammatory bowel disease (IBD), comprising ulcerative colitis (UC) and Crohn’s disease (CD), is a chronic inflammatory disorder of the gastrointestinal tract characterized by progressive and relapsing inflammation with heterogeneous clinical manifestations. The pathogenesis of IBD involves complex interactions between intestinal barrier dysfunction and dysregulated immune responses. Autophagy, an evolutionarily conserved cellular homeostasis mechanism, plays a dual role in IBD pathogenesis by maintaining cellular integrity and modulating immune responses. This process contributes to IBD immunopathology through multiple mechanisms, including pathogen clearance, immune cell regulation, inflammatory signaling modulation, and inflammasome suppression. Growing evidence has established autophagy as a critical regulator of intestinal inflammation. Here, we described the intricate relationship between autophagy dysregulation and IBD progression, highlighting potential therapeutic strategies targeting autophagy pathways, such as inflammasome inhibitors, gut microbiota modulators, and specific signaling pathway regulators in intestinal epithelial cells and macrophages. These autophagy-focused interventions represent promising therapeutic avenues for IBD treatment. Further elucidation of the autophagy–IBD axis may provide novel insights into disease mechanisms and therapeutic development for these complex disorders.